2001
DOI: 10.1034/j.1600-0838.2001.110606.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short‐term strength training on human skeletal muscle: the importance of physiologically elevated hormone levels

Abstract: The effect of strength training and endogenously elevated hormone levels (plasma testosterone, growth hormone (GH) and cortisol) was studied in 16 young untrained males, divided into an arm only training group, A, and a leg plus arm training group, LA, in order to increase circulating levels of anabolic hormones. Both groups performed the same one-sided arm training for 9 weeks, twice a week. Group A trained only one arm (AT), the contralateral arm serving as control (AC), whereas group LA additionally trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
0
15

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(154 citation statements)
references
References 0 publications
12
127
0
15
Order By: Relevance
“…The ~21% increase in 1RM biceps curl in L+A is in line with other studies using similar strength training intervention, while the ~14% increase in A is slightly below the expected improvement (McCall et al 1996;Moss et al 1997;Hansen et al 2001;McBride et al 2003). The observations of superior gains in 1RM biceps curl and CSA in the L+A arm indicates that the acute elevations in circulating hormones contributes to strength training adaptations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The ~21% increase in 1RM biceps curl in L+A is in line with other studies using similar strength training intervention, while the ~14% increase in A is slightly below the expected improvement (McCall et al 1996;Moss et al 1997;Hansen et al 2001;McBride et al 2003). The observations of superior gains in 1RM biceps curl and CSA in the L+A arm indicates that the acute elevations in circulating hormones contributes to strength training adaptations.…”
Section: Discussionsupporting
confidence: 89%
“…However, in the study by Hansen et al (2001) legs were also trained after arm exercises and a somewhat additive effect on isometric strength, but not on isokinetic and isotonic strength was reported. Another difference from the study by Walker et al is that in the present study, one arm was subjected to L+A training, while the other arm was subjected to the A training.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The results of this study will help practitioners and coaches to understand if the CLA supplementation can be useful to increase the testosterone synthesis immediately after an acute session of resistance exercise affecting the anabolic phase followed by each strength training session. It has previously been suggested that the acute elevation of testosterone could mediate an anabolic phase after each strength training session, when the muscle is exposed to the anabolic hormone only for a short period (13). Conjugated linoleic acid induced an increase in testosterone production in our in vitro experiments.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, all sets required 10 repetitions and a 90 second rest was set between trials. The range of elbow joint motions for the concentric part was fully extended from 145 to 155°, flexed and means velocities for one repetition including concentric and eccentric motions were in a range of 100-150°/s [13]. The second blood drawing was conducted 30 minutes after the strength training.…”
Section: Experimental Protocol and Proceduresmentioning
confidence: 99%